The Effect of MSCs Derived from the Human Umbilical Cord Transduced by Fibroblast Growth Factor-20 on Parkinson's Disease. (5th May 2016) - Jinfeng, Li; Yunliang, Wang; Xinshan, Liu; Shanshan, Wang; Chunyang, Xu; Peng, Xue; Xiaopeng, Yang; Zhixiu, Xu; Honglei, Yin; Xia, Cao; Haifeng, Duan; Bingzhen, Cao
Abstract : Cell therapy is a potential therapeutic approach for Parkinson's disease (PD). Mesenchymal stem cells derived from the human umbilical cord (hUC-MSCs) give priority to PD patients because of multiple advantages. The appropriate gene transduction of hUC-MSC before transplantation is a promising procedure for cell therapy. Fibroblast growth factor-20 (FGF-20) has been shown to protect dopaminergic neurons against a range of toxic insults in vitro. In this study, the hUC-MSCs were gene transduced with FGF-20, and then we transplanted them into the PD mice model. The results showed that MSC-FGF-20 treatment obviously improved the behavior of PD, accompanied by the increase of tyrosine carboxylase- (TH-) positive cell and dopamine (DA). Furtherly, immunohistochemistry disclosed that MSC-FGF-20 obviously promoted the degradation of nuclear factor- κ B (NF- κ B), a transcription factor that controls genes encoding proinflammatory cytokines, highly expressed in the nigrostriatal dopaminergic regions in PD patients. Therefore, MSC-FGF-20 has a potential for improving PD, closely related to the degradation of NF- κ B.